Women's entrepreneurship and ICTs - Ngwenya, Minenhle (Technical Centre for Agricultural and Rural Cooperation, 2012)
In Zimbabwe, the cost of cell phone usage remains quite high, but women entrepreneurs have benefited from improved access to mobile communication technology.